Potential areas for groundwater exploration in the Puyango Catamayo Hydrographic Demarcation, Ecuador, using a analytic hierarchy process based on GIS and remote sensing - V.X. Macas-Espinosa; K.F. López-Escobar (Revista de Teledetección)
The objective of this study is to apply geographic information systems and remote sensing techniques to map potential areas for groundwater exploration in the Puyango Catamayo hydrographic demarcation, based on free input data. The research’s primary data are a digital elevation model, satellite images, regional geology and rainfall. From the methodological point of view, Multi-Criteria Decision Analysis is applied, using an Analytic Hierarchy Process, which takes as thematic layers the  rock permeability, the rainfall, the drainage density,  the terrain slope, and the normalized difference vegetation index. Thus,  the Groundwater Potential Index is obtained, which is used to map potential areas for groundwater exploration. The resulting map is compared with the existing data of the water point inventory, generated by the Ecuador’s National Institute of Meteorology and Hydrology. Data validation by this method shows that 30% of the water points are located in areas not suitable for groundwater exploration, while 70% are in favorable areas.